The repressor activity of Even-skipped is highly conserved, and is sufficient to activate engrailed and to regulate both the spacing and stability of parasegment boundaries. - Fujioka, M.; Yusibova, G.L.; Patel, N.H.; Brown, S.J.; Jaynes, J.B. (Development, 2002)
During segmentation of the Drosophila embryo, even skipped is required to activate engrailed stripes and to organize odd-numbered parasegments. A 16 kb transgene containing the even skipped coding region can rescue normal engrailed expression, as well as all other aspects of segmentation, in even skipped null mutants. To better understand its mechanism of action, we functionally dissected the Even-skipped protein in the context of this transgene. We found that Even-skipped utilizes two repressor domains to carry out its function. Each of these domains can function autonomously in embryos when fused with the Gal4 DNA-binding domain. A chimeric protein consisting only of the Engrailed repressor domain and the Even-skipped homeodomain, but not the homeodomain alone, was able to restore function, indicating that the repression of target genes is sufficient for even skipped function at the blastoderm stage, while the homeodomain is sufficient to recognize those target genes. When Drosophila Even skipped was replaced by its homologs from other species, including a mouse homolog, they could provide substantial function, indicating that these proteins can recognize similar target sites and also provide repressor activity. Using this rescue system, we show that broad, early even skipped stripes are sufficient for activation of both odd- and even-numbered engrailed stripes. Furthermore, these 'unrefined' stripes organize odd-numbered parasegments in a dose-dependent manner, while the refined, late stripes, which coincide cell-for-cell with parasegment boundaries, are required to ensure the stability of the boundaries.